三明治型中心裂纹试样性能失配对材料拘束作用范围的影响研究 - 戴悦; 杨杰; 陈浩峰 (Jixie qiangdu)
Different property mismatched laboratory specimens with sandwich structure and center crack that contain the single-edge-notched bend（ SENB）,compact tension（ CT）,single edge-notched tensile（ SENT）,and central-cracked tension（ CCT） specimens were selected,and the FEM simulations based on GTN（ Gurson-Tvergaard-Needleman） damage model were used to further investigate the influence of property mismatch on the effect range of material constraint.The results show that the numerical value of the effect range is also influenced by the property mismatch.The effect range increases with increasing of the property mismatch.In addition,the strength of property mismatched structure has buckets effect,and the buckets effect is more obvious in high property mismatched structure.In the future,the correlation of the effect range of material constraint with geometry constraint and material constraint should be established,and the results can provide scientific support for the structure integrity assessment and the design of property mismatched structures.